¿Es viable la regulación a los juegos de azar virtuales incluidos en los videojuegos multijugador en línea para prevenir a niños y adolescentes de la ludopatía?: una aproximación desde el Derecho - Velásquez Santos, Carlos Alfredo (2021)
The Peruvian legal framework on gambling includes among its purposes the prevention of compulsive gambling in minors by restricting their access to gambling halls. However, there is a legal vacuum regarding virtual games of chance that can be found included in videogames, which are freely available to children and adolescents, representing a risk for this vulnerable sector that must be addressed. In this regard, the main objective of this research work is to present a proposal for the regulation of games of chance included in video games. For this, in the first chapter, the concept of video game, its market and its risks will be developed in detail. Likewise, their international regulatory age classification systems and their criticisms will be pointed out. In the second chapter, the Peruvian regulatory framework for gambling will be described, as well as the authorities in charge of it and a draft law that tried to regulate internet gambling. Finally, in the third chapter, it will be addressed the comparative experience regarding the regulation of games of chance included in videogames and the specific regulatory proposal for the Peruvian case will be presented.